Pengaruh Aksesibilitas Penyuluhan dan Kredit terhadap Efisiensi Usahatani Padi di Jawa - Achmad, Muchransyah; Hartoyo, Sri; Mangkuprawira, Tb. Sjafri; Kusnadi, Nunung (Jurnal Trikonomika, 2012)
Production inefficiency usually is analyzed by using two efficiency approaches, technical and allocative efficiency. This study performs direct calculations of the technical efficiency of rice farming in Java by using the stochastic frontier and inefficiency that influence on a model. The data consisted of the 2007 Patanas Data released by the Center for Socio Economic and Agricultural Policy, Agricultural Research and Development Agency, Ministry of Agriculture, conducted in three provinces of West Java, Central Java and East Java that are implemented in several major rice producing districts. The result of this study indicated that the production of paddy rice field in West Java, Central Java and East Java where positively influenced by the extensive paddy fields, the number of seeds used, urea fertilizer and ZA, TSP, KCL and NPK fertilizers as well as the number of labors family and non family. Accessibility factors on education, credit and extension service where significantly affected upon the inefficiency of in the province of West Java, Central Java and East Java.